Chemical and Lead Isotope characterisation of First World War shrapnel balls and bullets used on the Alpine Austrian–Italian Front - Latterza, Vittoria; Ros, Veronica; Turetta, Clara; Gabrieli, Jacopo; Cairns, Warren RL; Balliana, Eleonora; Baroni, Carlo; Salvatore, Maria Cristina; Bondesan, Aldino; Brabante, Carlo (Scientia Militaria - South African Journal of Military Studies, 2018)
Chemical and lead isotope characterisation was carried out on shrapnel balls and bullets dating back to the First World War (WWI). These ammunitions were widely utilised in the Alpine Austrian–Italian front located in the Italian Alps. The investigation has been performed using inductively coupled plasma quadrupole mass spectrometry equipped with an octopole reaction system (ORS-ICP-QMS). The main goal of this work was to identify the elemental and lead isotope composition of raw materials and to discriminate between the military objects analysed. The results of multi-elemental analysis indicate that the shrapnel ball samples consisted of soft Pb or hard Pb with Sb depending on the use, the weapon type and the specific nation. The Italian shrapnel balls were made from hard Pb, as opposed to those of the Austrian–Hungarian samples. Through the investigation of lead isotope ratios, it has been possible to differentiate most of the Italian shrapnel balls from those of Austrian–Hungarian origin. Furthermore, some Italian shrapnel balls had a different lead isotope composition depending on their calibre. The elemental composition and lead isotopic signature of bullets show a clear discrimination between the external jacket and the core in relation to projectile type and nationality. The bullet cores consist of Pb–Sb alloy regardless of the region of origin. This work allowed us to investigate the potential applications of trace elements and lead isotope analyses to discriminate military artefacts of different origins.